2000
DOI: 10.1023/a:1007109120558
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Human renal calculi surgically removed from kidney stone patients were obtained and chemically analysed. Stones with CaOx (calcium oxalate) as the major component were washed in 0.15 M NaCl with gentle stirring for 48 h and then pulverised to a fine powder. The powder was extracted with 0.05 M EGTA, 1 mM PMSF and 1% beta-mercaptoethanol for 4 days at 4 degrees C, the suspensions and the supernatants obtained were filtered through an Amicon Model 200 apparatus (mol. wt. cut off of 10,000 daltons) under nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The supernatant of EGTA extract was filtered through Amicon ultra centrifugal filter device with 3kDa molecular weight cut off at 4°C and concentrated it. Whole EGTA extract and greater than 3 kDa fractions were stored at −20°C for further studies [15].…”
Section: Methodsmentioning
confidence: 99%
“…The supernatant of EGTA extract was filtered through Amicon ultra centrifugal filter device with 3kDa molecular weight cut off at 4°C and concentrated it. Whole EGTA extract and greater than 3 kDa fractions were stored at −20°C for further studies [15].…”
Section: Methodsmentioning
confidence: 99%
“…Our research group has been conducting many studies to explore the organic matrix of renal stone and revealed the presence of a 66 kDa stimulator of calcium oxalate crystal growth in the human renal calculi extract [6]. Later they investigated the activity of high and low molecular weight biomolecules present in the matrix of human CaOx stones not only on the initial mineral phase formation of calcium and phosphate (CaP) but also on its growth and demineralization of the preformed mineral phase [226].…”
Section: Matrix Componentsmentioning
confidence: 99%
“…However, approximately 75% of stones are primarily calcium oxalate, but up to 50% of these include calcium hydroxyl phosphate (brushite or calcium hydroxyapatite) in trace or greater amounts; 10–20% are composed of magnesium ammonium phosphate (struvite or triple phosphate); 5% are composed of urate; and 1-2% are composed of cystine [4, 5]. With its multifactor etiology and high rate of recurrences, urinary tract stone disease provides a medical challenge [6]. There is thus a pressing need to prevent this disease and its recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…The solutions of 7. accomplished by comparing the turbidity slope of the varying concentrations of cystone or AEAR with the control by the succeeding formula. 15 However Tsi was the nucleation turbidity slope in the existence of an inhibitor sample, i.e., cystone/AEAR and Tsc was the nucleation turbidity slope in the absence of the inhibitor (control).…”
Section: In Vitro Caox Crystallization Model 251 Crystal Nucleationmentioning
confidence: 99%